Is European school transport safe?-The need for a "door-to-door" perspective - Anund, A.; Dukic, T.; Thornthwaite, S.; Falkmer, Torbjorn (Springer, 2011)
Purpose: To identify and establish the number and aetiology behind children being killed or injured during school transport from a door-to-door perspective by using experience from Sweden and the UK. Methods Available crash data were analysed. Results: In total, 361 children in Sweden during 1994–2001, i.e. 24% of the 1,515 identified children aged 6–16 who were injured or killed were identified in 256 school transport events. The predominant reason for being killed or injured when travelling on school transportation was when children were outside the bus (74%), either when passing the bus to cross the street, running in front of the bus (21%) or behind the bus (30%). Contrary to the general belief that children older than 12 are mature enough to handle traffic, more than 50% of the fatal injuries in Sweden affected children aged 13–16. Similar results were found in the UK. The afternoon school journeys, pedestrians after alighting from the bus, and those in situations that deviated from their normal routine were found to be particularly vulnerable. Conclusions The travel chain perspective/or door to door perspective offers a promising approach for understanding school transport risks and for identifying effective countermeasures; including around bus stops and on the way to/from the bus stop. Data collection needs to be revised to reflect this approach.